ANALISIS ARUS DAN TEGANGAN PADA RANGKAIAN KOMBINASI MENGGUNAKAN SIMULATOR LIVEWIRE - Jonathan Farrel Akbar; Noval Resti Ardiansyah; Kayla Luna Pasha; Aryanti Aryanti (JURNAL TELISKA, 2025)
This article discusses the use of LiveWire software as an interactive simulation medium for analyzing current and voltage in mixed resistor circuits, which are a combination of series and parallel circuits. This study aims to demonstrate how LiveWire can be used as a learning tool to understand basic electrical concepts more effectively and efficiently. Through digital simulation, users can accurately observe the distribution of current, voltage, and power in each resistor without the need for physical measuring instruments in the laboratory. The simulation results are then compared with theoretical calculations based on Ohm's Law, showing a very high degree of conformity with insignificant differences in values. This proves that LiveWire is capable of representing the behavior of electrical circuits realistically. In addition to simplifying the design and analysis process, the use of LiveWire also improves practitioners' understanding of the relationship between current, voltage, and resistance. Thus, LiveWire can be used as an interactive, safe, and efficient digital learning medium to support electronics practicum activities.